Worterbuch der Textilveregelung = Dictionary of textile finishing - Rouette, Hans-Karl, 1939- (Woodhead publishing in textiles., 2002)
In the Dictionary of textile finishing the textile engineer will find the correct technical terms for 16,000 keywords within their field of activity in the German language and vice versa. The dictionary is the link between the Encyclopedia of Textile Finishing and the Lexikon der Textilveredelung from the same author. It is supplemented by a comprehensive collection of acronyms in the textile field (approx. 500 acronyms and their meanings). This book is essential for all textile engineers in the textile industry and textile machine producing industry, researchers, students, translators and journalists in textile science.